2020
DOI: 10.3390/plants9070863
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Composition and Some Nutritional Parameters of Sweet Pepper from Organic and Conventional Agriculture

Abstract: The increasing demand of organic agriculture (OA) is based on the consumer’s belief that organic agricultural products are healthier, tastier and more nutritious. The effect of OA and conventional agriculture (CA) methods on the elemental compositions of green and red sweet peppers were studied. The highest concentrations of Ca, Cu, K and P occur in peppers from OA in both states of ripeness, with emphasis on Ca and K contents. Furthermore, the principal component analysis (PCA), points out to a clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…These elements help to increase the cell wall thickness of cherry tomato fruits [ 17 , 18 , 19 ]. Guilherme et al [ 20 ] reported that organically grown sweet peppers showed higher level of firmness than conventionally grown sweet peppers. They also mentioned that organically grown sweet peppers had the highest Ca content.…”
Section: Physicochemical Quality Of Fresh Producementioning
confidence: 99%
See 4 more Smart Citations
“…These elements help to increase the cell wall thickness of cherry tomato fruits [ 17 , 18 , 19 ]. Guilherme et al [ 20 ] reported that organically grown sweet peppers showed higher level of firmness than conventionally grown sweet peppers. They also mentioned that organically grown sweet peppers had the highest Ca content.…”
Section: Physicochemical Quality Of Fresh Producementioning
confidence: 99%
“…There was no difference between the organic and the conventionally grown apples and carrots [ 23 , 28 ]. Conventionally grown sweet peppers showed higher titratable acidity than the organic ones [ 20 ].…”
Section: Physicochemical Quality Of Fresh Producementioning
confidence: 99%
See 3 more Smart Citations